Clinicopathologic Characteristics of Thyroid-like Low-grade Nasopharyngeal Papillary Adenocarcinoma: A Case Report. Issue 8 (September 2019) - Li, Liang; Zhou, Fengjuan; Lin, Fanzhong; Han, Cuihong
Abstract : Thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPPA) is an extremely rare neoplasm. It morphologically resembles papillary thyroid carcinoma and is immunochemically positive for thyroid transcription factor 1. Herein, we reported a case of TL-LGNPPA in a female patient of 35 years old. She felt pharyngeal foreign body sensation of unknown cause and subsequently developed dyspnea after activities. Nasopharyngeal plain computerized tomography showed no abnormalities, but laryngoscopy showed a peanut-sized smooth neoplasm with a pedicel at the posterior edge of the nasal septum. The mass was completely resected by nasopharyngoscopy. Histologic examination showed the tumor was composed of papillary configuration and tubular glands; each papilla was covered with cuboidal or columnar epithelial cells; tubular architecture and spindle cell component were also observed; some tumor cells had psammoma bodies. Immunohistochemically, tumor cells were positive for CKpan, CK7, CK19, VIM, and thyroid transcription factor 1, but negative for thyroglobulin, CK20, S-100, P63, P40, smooth muscle actin, CDX-2, and glial fibrillary acidic protein. This patient was diagnosed with TL-LGNPPA and followed up for 16 months, and metastasis and recurrence were not observed.